2020
DOI: 10.1021/acs.est.9b05651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural Organic Matter on Plutonium Vadose Zone Migration from an NH4Pu(V)O2CO3(s) Source

Abstract: We investigated the influence of natural organic matter (NOM) on the behavior of Pu(V) in the vadose zone through a combination of field lysimeter and laboratory studies. Well-defined solid sources of NH 4 Pu(V)O 2 CO 3 (s) were placed in two 5-L lysimeters containing NOM-amended collected from Savannah River Site or unamended vadose zone soils and exposed to three years of natural South Carolina, USA meteorological conditions. The lysimeter soil cores were removed from the field, used in desorption experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Indeed, HA can significantly accelerate Pu oxidation to Pu­(V/VI). Our results suggest that the observations and conceptual models of enhanced Pu migration reported in the studies by Molz et al and Maloubier et al may indeed be explained by the transient Pu oxidation that occurs during the infiltration of H 2 O 2 -containing water into sediments. , However, high concentrations of NOM may also decrease Pu migration by facilitating the reduction of Pu­(V/VI), as observed by Maloubier et al Indeed, the subsurface is a highly complex and heterogeneous environment that can exhibit dynamic geochemical conditions compared to systems presented in this study. Ongoing research will extend the framework developed here by evaluating the role of numerous variables (e.g., extended pH range, H 2 O 2 concentrations, and NOM compositions).…”
Section: Environmental Implicationssupporting
confidence: 76%
See 4 more Smart Citations
“…Indeed, HA can significantly accelerate Pu oxidation to Pu­(V/VI). Our results suggest that the observations and conceptual models of enhanced Pu migration reported in the studies by Molz et al and Maloubier et al may indeed be explained by the transient Pu oxidation that occurs during the infiltration of H 2 O 2 -containing water into sediments. , However, high concentrations of NOM may also decrease Pu migration by facilitating the reduction of Pu­(V/VI), as observed by Maloubier et al Indeed, the subsurface is a highly complex and heterogeneous environment that can exhibit dynamic geochemical conditions compared to systems presented in this study. Ongoing research will extend the framework developed here by evaluating the role of numerous variables (e.g., extended pH range, H 2 O 2 concentrations, and NOM compositions).…”
Section: Environmental Implicationssupporting
confidence: 76%
“…For surface water and groundwater interactions, enhanced Pu migration has been observed at the Savannah River site due to Pu­(IV) oxidation to Pu­(V) from infiltrating and oxidizing rainwater . However, a quite recent study showed that the presence of NOM significantly limited Pu migration through reduction of Pu­(V) and increased Pu sorption to soils . These contrasting observations suggest that our understanding of the impact of NOM on Pu migration in surface and groundwater is incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations